Performance Evaluation of Historical Masonry Structure - Adhikari, Abish Shankar; Nepal, Shraddha; Neupane, Ishaan; Karmacharya, Sunaina; Maharjan, Niya; Dangol, Kripanjal; Paudel, Satish (International Journal on Engineering Technology and Infrastructure Development, 2025)
Architectural heritage represents an invaluable reflection of the intellectual depth and cultural diversity of contemporary societies, making the structural analysis and safety assessment of historical buildings critically important. Consequently, societies have encouraged the development of specific legislation focused on the protection and preservation of their historical and cultural heritage. Studies have revealed that these structures are vulnerable to powerful outside forces including blasts, high winds, and earthquakes. Many earthquakes strengthening and retrofitting methods for masonry elements and structures have been developed and implemented over the last few decades. The methods utilized to strengthen and adapt Unreinforced Masonry (URM) buildings subjected to seismic and high stress are reviewed and summarized in this study based on prior research. After the performance evaluation of these structures suitable strengthening measures will be explored. These strengthening and retrofitting techniques aim to improve the overall integrity of the masonry structure, decrease the effects of external forces, and increase the load-bearing capability of individual elements.